Fenomenology Study : The role of Occupational Health Nurses (OHN) in Emergency and Disaster Services, Qualitative Research - Faiqh Albyn, Devanda; Achkanul Hak, Denny; Ribowo, Didit (Medical : Jurnal Kesehatan dan Kedokteran, 2024)
Abstract: In the 2022 National K3 Profile, there is still a high number of PAK and KK based on global data released by the International Labor Organization (ILO), that the number of KK and PAK cases in the world reached 430 million per year, consisting of 270 million (62.8% ) KK cases and 160 million (37.2%) PAK cases, and caused the death of 2.78 million workers. every year. industries in 49 countries include occupational health physicians, occupational health nurses, occupational hygienists, safety engineers, ergonomists/physiotherapists, and psychologists to provide comprehensive K3 services. This research method is qualitative research with a phenomenological research design and uses exploratory descriptive analysis. Data collection used interview and observation methods, carried out at oil and gas and plantation companies. The results achieved in this research concluded that OHN or company nursing staff have a very important role in supporting occupational health programs and occupational welfare programs. As in interviews conducted with 3 participants, it was revealed that the role of OHN is very comprehensive. All worker activities in the company must be supervised by OHN. Apart from that, by empowering OHN within the company, management only needs to facilitate training and knowledge upgrades for the Occupational Health and Safety team for the company's financial efficiency. Keywords: - Occupational Health Nurse, Sport Injury, Wellness & Occupational Health Programe